Effect of two cooking methods and temperature on oxidation and microbiological properties of breakfast sausage (2015)
Sausages were prepared from 65% meat, 20% lard, 3.5% binder, 2.01% curing salt, 1% sugar, 0.30% phosphate, 4% ice water, 2% dry spice, and 2.19 wet spices. A set of five samples were boiled in a water bath while another set were baked at temperatures of 80, 90, 100, 110 and 120 °C. The effect of cooking method and temperature was tested on oxidative and microbiological properties of breakfast sausage. The oxidative properties were evaluated using iodine value, acid value and thiobarbituric acid reactive substances (TBARS) assays. Three culture media were used to measure the microbial status of product using Nutrient Agar (NA) for total aerobic count, Potato Dextrose Agar (PDA) for yeast and mould count and Ethyl Methanesulfonate (EMS) for coliform bacteria count. Significant differences were observed for all the parameters measured at a significant level of 5%. Iodine value measures the level of unsaturated fatty acid, Iodine value ranged from 2.54 to 6.86 mg/g. Baking at 90°C gave the highest value, while boiling at 100°C and baking at 120°C had the lowest values. Acid value had boiling at 100°C giving the highest value and baking at 80°C giving the least. TBARS value showed that boiling at 120°C had the highest value, while boiling at 90°C gave the lowest value. Total aerobic count was high at 110°C for baking and boiling at 100°C. Total coliform bacteria count was high at boiling at 90°C. Fungi growth in the sausage was generally low, baking at 80°C had the highest count and least count was observed for boiling at 80°C and baking at 90°C. In conclusion, the oxidative and microbiological properties of breakfast sausage as influenced by cooking method and temperature showed the best cooking method and temperature interaction to be baking at 90°C and 100°C.